2019
DOI: 10.1016/j.dam.2019.01.039
|View full text |Cite
|
Sign up to set email alerts
|

The expanding search ratio of a graph

Abstract: We study the problem of searching for a hidden target in an environment that is modeled by an edge-weighted graph. A sequence of edges is chosen starting from a given root vertex such that each edge is adjacent to a previously chosen edge. This search paradigm, known as expanding search was recently introduced by Alpern and Lidbetter (2013) for modeling problems such as searching for coal or minesweeping in which the cost of re-exploration is negligible. It can also be used to model a team of searchers success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…For normalized objectives (Angelopoulos et al, 2019) recently studied expanding search in a fixed (finite) graph in which the Hider can only hide on vertices. In terms of finding a strategy of optimal deterministic competitive ratio (Angelopoulos et al, 2019) showed that the problem is NP-hard, and gave a 4 ln 4 approximation. Concerning the randomized competitive ratio, the same work presented a strategy that is a 5/4-approximation in the special case of tree graphs.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…For normalized objectives (Angelopoulos et al, 2019) recently studied expanding search in a fixed (finite) graph in which the Hider can only hide on vertices. In terms of finding a strategy of optimal deterministic competitive ratio (Angelopoulos et al, 2019) showed that the problem is NP-hard, and gave a 4 ln 4 approximation. Concerning the randomized competitive ratio, the same work presented a strategy that is a 5/4-approximation in the special case of tree graphs.…”
Section: Related Workmentioning
confidence: 99%
“…In this section we give a search strategy that is a 5/4-approximation of the optimal randomized search. This is inspired by the strategy of (Angelopoulos et al, 2019) for the discrete case, namely for searching in a given graph when the Hider can only hide at a vertex.…”
Section: A 5/4-approximation Of the Randomized Competitive Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…This type of payoff function was introduced in search theory independently by Beck (1964) and Bellman (1963) in the context of the linear search problem, later extended by Gal (1974). The linear search problem is framed in a continuous setting, but multiplicative regret for search theory has also been studied in a discrete setting in Koutsoupias et al (1996) and Angelopoulos et al (2016).…”
Section: Search Cost Regretmentioning
confidence: 99%